PELATIHAN PENULISAN ARTIKEL JURNAL INTERNASIONAL BEREPUTASI BAGI DOSEN-DOSEN PERGURUAN TINGGI ISLAM SWASTA (PTAIS) - Luluk Sri Agus Prasetyoningsih; M. Faruq Ubaidillah; Nuris Shobah; Khoirotun Nisak; Sonny Elfianto (Jurnal Praksis dan Dedikasi Sosial (JPDS), 2023)
REPUTABLE INTERNATIONAL JOURNAL ARTICLE WRITING TRAINING FOR PRIVATE ISLAMIC HIGHER EDUCATION LECTURERSThis community service activity aims to provide training to lecturers in producing journal articles that can be submitted for publication in national and international journals. This activity is carried out through online and offline seminars. The executor of this activity is theÂ University of Islam Malang under the auspices of the Institute for Research and Community Service UNISMA. This activity was carried out at STAI Darul Ulum Banyuanyar Pamekasan Madura. The method of implementing the activity consists of several stages. The first stage is planning through discussions with the organizers to meet participants' expectations regarding the benefits of training activities. The second stage is the delivery of material and discussions through online seminars (zoom meetings) and offline or face-to-face. The third stage is further online discussion with participants who need additional explanation. Based on the satisfaction survey obtained from the participants after the activity took place, this activity was in accordance with the needs of the participants and was very useful for the participants as well as motivating the participants to improve the quality of research articles so that they could be submitted for publication in national and international journals.Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memberikan pelatihan kepada dosen dalam menghasilkan artikel jurnal yang dapat diajukan untuk publikasi di jurnal nasional dan internasional. Kegiatan ini dilaksanakan melalui seminar online dan offline. Pelaksana kegiatan ini adalah Universitas Islam Malang di bawah naungan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) UNISMA. Kegiatan ini dilaksanakan di STAI Darul Ulum Banyuanyar Pamekasan Madura. Metode pelaksanaan kegiatan terdiri dari beberapa tahapan. Tahap pertama adalah perencanaan melalui diskusi dengan pihak penyelenggara untuk memenuhi harapan peserta mengenai manfaat dari kegiatan pelatihan. Tahap kedua adalah penyampaian materi dan diskusi melalui seminar online (zoom meeting) dan offline atau tatap muka. Tahap ketiga adalah diskusi online lebih lanjut dengan peserta yang membutuhkan penjelasan tambahan. Berdasarkan survey kepuasan yang didapat dari peserta setelah kegiatan berlangsung, kegiatan ini sesuai dengan kebutuhan peserta dan sangat bermanfaat bagi peserta serta memotivasi peserta untuk meningkatkan kualitas artikel penelitian agar dapat diajukan untuk dipublikasikan di jurnal nasional dan internasional.